أسس العلاقات الأسرية من خلال القرآن الكريم - سويد, وفاء; كشي, الرميصاء (University of Eloued-جامعة الوادي, 2022)
"نبدأ بسم الله والصلاة والسلام على خير الأنام رسول الله صلى الله عليه وسلم سيد الأنبياء والمرسلين محمد الذي جاء رحمة للعالمين ،وبعد: جاء هذا البحث بعنوان أسس العلاقات الأسرية من خلال القرآن الكريم ومن أبرز أهدافه أنه يلفت النتباه إلى الأسس المتعلقة بالعلاقة بين الزوجين ثم بين الأبناء والآباء ثم الأخوة والأقارب من خلال الوصف التحليلي للحقوق والواجبات المترتبة عن كل فرد منهم . فمن النتائج البارزة في البحث أن الأسرة تمتاز كمنظمة اجتماعية بأنها تمارس نفوذا كبيرا على أفرادها على اعتبار الأسرة . فهي أصغر أحجام المنظمات الاجتماعية من حيث الحجم وذلك للتفاعل بين أفرادها . وهي أيضا حجر الزاوية في البناء الاجتماعي باعتبارها نقطة الارتكاز التي ترتكز عليها بقية منظمات المجتمع الاجتماعية ولأنها القاعدة التي بصلاحها يصلح المجتمع كله وبفسادها يفسد المجتمع كله . أن الأسرة تمارس ضبطا اجتماعيا له أهمية على أفرادها ،وهذا الضبط يأتي من جهة الأحكام الزوجية وإصلاح وحل جميع المشاكل التي قد تحل بالعلاقات الزوجية. لكل فرد من أفراد الأسرة حقوق وواجبات تجاه بعضهم وعلى كل فرد من أفرادها التحلي بروح المسؤولية فمن الحقوق المترتبة عن الزوج تجاه الزوجة :حسن المعاشرة ،وحل الاستمتاع والنفقة وأما واجبات الزوجة فهي طاعة الزوج من غير معصية ،والقرار في المنزل ... وأما الحقوق التي بين الآباء والأبناء فهي تبدأ من حق الأبناء في اختيار الأم الصالحة والاسم الحسن ،الحضانة ،الرضاعة، النفقة،....أما واجباتهم تجاه والديهم فالبر بهما ،والاحسان إليهما ومعاملتهما بأسلوب متأدب .... ""We begin in the name of God, and may blessings and peace be upon the best of creatures, the Messenger of God, may God’s prayers and peace be upon him, the master of the prophets and messengers, Muhammad, who came as a mercy to the worlds. Sons, fathers, then brothers and relatives through an analytical description of the rights and duties of each of them. One of the prominent results of the research is that the family is characterized as a social organization in that it exercises a great influence on its members, considering the family. They are the smallest sizes of social organizations in terms of size for the interaction between their members. It is also the cornerstone of the social construction, as it is the fulcrum on which the rest of the social organizations of society rest, and because it is the base that, with its goodness, reform the whole society, and with its corruption corrupting the whole society. The family exercises social control that is of importance to its members, and this control comes from the point of view of marital provisions and the reform and solution of all problems that may solve marital relations. Every member of the family has rights and duties towards each other, and each of its members has to show a spirit of responsibility. Among the rights deriving from the husband towards the wife are: good cohabitation, the solution of enjoyment and alimony. As for the duties of the wife, they are obedience to the husband without disobedience, and the decision in the home... As for the rights that are between fathers and children, they start with the children’s right to choose a good mother and a good name, custody, breastfeeding, alimony…."
مذكرة ماستر
Keywords: الأُسس – العلاقات -الأُسرة - العلاقات الأسرية – أسس العلاقات الأسرية; foundations - relationships - family - family relationships - foundations of family relationships